Digitizing the Logistics Business in India- A Leadership Case Study - Vinayak Vishwakarma (European Economic Letters (EEL), 2024)
The logistics industry is very important for any growing country. China has already shown how strong its logistics industry can be, and India will soon follow suit. Key factors that are propelling market growth are the growing amount of business data and the automation of tasks in fields like retail, transportation, education, and healthcare. All other businesses depend on the transportation and logistics sector to make moving goods by air, land, or sea easier.